Adaptive reshaping of the hormonal phenotype after social niche transition in adulthood. Issue 1928 (10th June 2020) - Mutwill, Alexandra M.; Zimmermann, Tobias D.; Hennicke, Antonia; Richter, S. Helene; Kaiser, Sylvia; Sachser, Norbert
Abstract : Phenotypic plasticity allows individuals to adjust traits to the environment. Whether long-term adjustments of the phenotype occur during later life stages is largely unknown. To address this question, we examined whether hormonal phenotypes that are shaped by the environment during adolescence can still be reshaped in full adulthood. For this, guinea pig males were either housed in mixed-sex colonies or in heterosexual pairs. In adulthood, males were individually transferred to pair housing with a female. This way, a social niche transition was induced in colony-housed males, but not in pair-housed males. Before transfer, corresponding to findings in adolescence, adult colony-housed males showed significantly higher baseline testosterone levels and lower cortisol responsiveness than pair-housed males. One month after transfer, the hormonal phenotype of colony-housed males was changed towards that of pair-housed males: animals showed comparable baseline testosterone levels and cortisol responsiveness was significantly increased in colony-housed males. This endocrine readjustment builds the basis for an adaptive behavioural tactic in the new social situation. Thus, an adaptive change of the behavioural phenotype may still occur in adulthood via modification of underlying mechanisms. This suggests a greater role for developmental plasticity in later life stages than is commonly presumed.